ACROSS THE AGES: THE DEVELOPMENT OF ISLAMIC SCHOOLS OF THOUGHT AND THEIR EXISTENCE IN SOUTH EAST ASIA - Rambe, Ahmad Yahdil Fata; Tanjung, Miftah Daud; Hidayati, Nur; Enjliana, Enjliana; Zakaria, Abd Razak (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2024)
The history of Islam is long and varied in the form of religious schools, thoughts and practices. Analysis of Islamic thought in Southeast Asia has a rich diversity, reflecting various historical, cultural and social contexts. This research aims to determine the development of Islamic thought in Southeast Asia and find out the implications of the development of Islamic thought in Southeast Asia in facing changing times. The method used in this research is library research. Library research is research where the data or materials needed to complete the research come from libraries in the form of books, encyclopedias, dictionaries, journals, magazines and so on. The research results show that schools of Islamic thought in Southeast Asia have experienced a complex journey, adapting to social, political and cultural changes. This evolution not only enriches the cultural diversity of this region, but also reflects the power of adaptation and resilience of schools of thought in facing the dynamics of the times. Key figures, such as ulama, intellectuals and philosophers, have played an important role in shaping and adapting Islamic thought to local realities. The implications of the development of Islamic thought highlight the ability of religion to adapt to rapid changes in times, including responses to globalization and modernization. New thoughts and reinterpretations of traditional concepts have emerged as an effort to answer the challenges of an ever-evolving era. Keywords: Development, Schools of Islamic Thought, Southeast Asia